RESPONSE OF LOCAL ORANGE TRANSPLANTS TO BIO AND ORGANIC FERTILIZERS AND SPRAYING WITH MORINGA LEAVES EXTRACT - Fatima Saad Hameed AL-Marsoumi,; Mustafa, E. A. AL-Hadethi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This experiment was carried out in 2023 season of spring and fall growth cycle in a private canopy in Al-Radwaniyah city, Baghdad Governorate, study included addition of bacterial biofertilizer at four treatments: no addition (A1),  addition of Stenotrophomonas maltophilia bacteria (A2) , addition of Azospirillum brasilense bacteria (A3) and addition of both types of bacteria (A4) and organic fertilizer (Decomposing buffalo manure) at three levels (0, 250 and 500 g.soil-1), which are symbolized by B0, B1, and B2, respectively Added once during the spring and fall growing cycle, and spray moringa extract at three levels (0, 20 and 40 g.L-1), which are symbolized M0, M1, and M2, respectively spray 5 times every 15 days. Treatments were replicated three times at factorial experiment in a RCBD and thus number of transplants used was 108. Experimental results showed that adding two types of bacteria (A4) and buffalo manure at a level of 500 g.soil-1 (B2) and spraying moringa extract at a concentration of 40 g.L-1 (M2) as interaction treatment A4B2M2 produced best results in shoot  number, stem diameter,  leaf potassium and iron percent %, and epidermal and spongy cells layers thickness, (25.00, 41.00) shoot.plant-1, (14.247, 5.283) mm, (2.980, 2.885) %, (215.8, 220.7) mg.kg-1 for two growing seasons, respectively, and (48.60, 108.4) micrometer, respectively compared to control treatment.